P-148 Discovery of Novel Oral Peptide Antagonists of IL-23 Receptor that Are Efficacious in a Rat Model of IBD. (March 2016) - Bhandari, Ashok; Cheng, Xiaoli; Bourne, Greg; Frederick, Brian; Zhang, Jenny; McMahon, Jaimee; Celino, Herodion; Zemede, Genet; Tran, Vinh; Dogra, Mridula; Bai, Lu; Annamalai, Thamil; et al.
Abstract : Background: The heterodimeric IL-23 receptor is comprised of the IL-12Rβ1 subunit in complex with IL-23R subunit. The ligand IL-23 is also a heterodimer of the unique p19 subunit coupled with the common p40 subunit shared with IL-12. Binding of IL-23 ligand to the IL-23R complex leads to phosphorylation of STAT3, and IL-23-dependent expression of pro-inflammatory cytokines. Clinical trials in Crohn's Disease or psoriasis with ustekinumab and briakinumab (which target the common p40 subunit) and tildrakizumab, guselkumab, MEDI2070, and BI-655066 (which target the unique p19 subunit of IL-23) highlight the potential of IL-23 signaling blockade in treatment of human inflammatory diseases. The aim of this study is to develop orally stable IL-23R antagonist peptides that act locally in the intestinal tissue for treatment of IBD. Methods: Potent, selective and orally stable peptide antagonists of IL-23R were identified through a combination of phage display technology and medicinal chemistry. To evaluate oral stability, the peptides were incubated in a variety of ex vivo intestinal/colonic washes or simulated gastric/intestinal fluids, and half-lives determined by mass spectrometry. Pharmacokinetic (PK), pharmacodynamic (PD) and colitis studies were conducted in rats. Results: Using a combination of phage display technology and medicinal chemistry, we identified functional inhibitory peptides of IL-23R that are stable in assays that mimic the harsh redox and proteolytic conditions of the GI environment. These peptides potently neutralize IL-23-mediated STAT3 signaling in the transformed human B lymphoblast DB cell line, and block IL-23 stimulated IFNg release from human primary NK cells. They are also active against the rat and cynomolgus monkey IL-23R. The peptides do not block the interaction between IL-6 and IL-6R or antagonize the IL-12 signaling pathway. In PK studies, oral dosing of the peptides results in high exposure in GI tissues, but very low exposure in the blood. In a rat TNBS (2, 4, 6-trinitrobenzenesulfonic acid)-induced acute colitis model, oral dosing of the peptides caused a significant reduction in neutrophil infiltration as measured by myeloperoxidase (MPO) activity, and a reduction in inflammation and other disease parameters as assessed by histopathology. These in vivo activities of the peptides were comparable to that of an anti-IL-23p19 mAb. Conclusions: We have discovered a suite of potent, selective, and orally efficacious IL-23R peptide antagonists that are promising GI restricted therapeutics for the treatment of IBD. Peptides are effective and comparable to an anti-IL-23p19 monoclonal antibody in attenuating colitis in a TNBS-induced rat colitis model. PK studies show these peptides have significant exposure in intestinal tissues, but not blood and urine indicating the exposure of these peptides is gut-restricted, and supports the potential of locally blocking IL-23 signaling while minimizing immunogenicity and the risk of opportunistic infections associated with systemically delivered immunosuppressants and biologics.